Evaluasi Pergerakan Gigi Insisif Menggunakan Desain Alat Ortodonsi Terbaru dengan Gaya Mekanis yang Berbeda - Hafiedz Maulana (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2016)
The purpose of orthodontic treatment is to correct dental malocclusion, which involved periodontal tissue remodeling process. Removable orthodontic appliance application was resulted a tipping tooth movement. Therefore, this research will develop a new orthodontic appliance design which is expected to generate closely to bodily tooth movement. The aim of this study was to evaluate the incisor tooth movement using a new orthodontic appliance design with different mechanical force applications. 28 Wistar rats were divided into 4 groups, a control group without orthodontic appliances (K), experimental group with 10 grams force (grf) of orthodontic appliances (P1), 20 grf (P2), and 30 grf (P3). Incisor distance measurement and roentgenogram evaluation were performed after seven days of orthodontic appliances application. The results of this study showed that the largest distance of incisor seen in P3 group and there is not a statistically significant difference between P1 and P2. Roentgenogram evaluation shows that all of orthodontic appliance force produced a bodily tooth movement.